Simultaneous efficacy of IL-15 and the HSP70 fragments in increasing immunostimulatory effects of a HIV-1 DNA vaccine candidate against SCR HIV-1 - Mehrshad Fekri; Azam Bolhassani; Monireh Movahedi; Fereshteh Rahmati (PLoS ONE, 2025)
Interleukin (IL)-15 serves as a potent adjuvant that can enhance T cell-directed vaccine responses. Moreover, heat shock proteins (HSPs) have been used as potent adjuvants in immunotherapy of tumors and infectious diseases, as well as in vaccine development. In this study, we evaluated the ability of IL-15 and HSP70 fragments (C-terminal (CT)-Hsp70 and N-terminal (NT)-Hsp70) to act as adjuvants for enhancing the immunostimulatory effects of a HIV-1 DNA vaccine candidate against single-cycle replicable (SCR) HIV-1. These adjuvants were administered individually and in combination with the HIV-1 Nef antigen candidate in BALB/c mice. The Nef, CT-Hsp70-Nef, NT-Hsp70-Nef and IL-15 genes were individually subcloned into the eukaryotic expression vector pVAX-1. Our results showed that the linkage of the CT-Hsp70 or the NT-Hsp70 gene to the Nef gene could significantly increase immune responses compared to the Nef gene alone ( p < 0.05). Moreover, the combination of pVAX-IL-15 with DNA constructs could significantly augment immune responses. Indeed, the combination of pVAX-IL-15 with pVAX-CT-Hsp70-Nef or pVAX-NT-Hsp70-Nef could substantially increase immune responses compared to pVAX-Nef combined with pVAX-IL-15 ( p < 0.05). Notably, the pVAX-CT-Hsp70-Nef construct, alone or combined with pVAX-IL-15, could significantly enhance immune responses to a greater extent than pVAX-NT-Hsp70-Nef with or without pVAX-IL-15 ( p < 0.05). In addition, we demonstrated that the highest secretion of total IgG antibody, interferon (IFN)- γ , and granzyme B was observed in the group receiving pVAX-CT-Hsp70-Nef combined with pVAX-IL-15, suggesting a shift in immune responses toward T helper type 1 (Th1) and cytotoxic T lymphocyte (CTL) activities. Furthermore, the pVAX-CT-Hsp70-Nef combined with pVAX-IL-15 regimen could maintain IFN-γ secretion after infection of mouse splenocytes with SCR HIV-1. Overall, our findings indicated that the concurrent use of two adjuvants—CT-Hsp70 and IL-15—effectively enhances antigen-specific immune responses. This regimen could be utilized as a vaccine candidate for boosting effective immune responses against HIV-1 infection.